Building in timber - room modules - Huß, Wolfgang,Kaufmann, Matthias,Merz, Konrad (DETAIL Business Information GmbH, 2019)
Ongoing urbanisation requires rapid, low-emission construction methods. Architects, investors and politicians are on the hunt for housing solutions that are fast and cost-effective, yet sustainable and flexible.Timber room modules meet all of these requirements: flexibility, variability, low construction and operating costs, short construction times thanks to high rates of prefabrication, a pleasant living environment, easy dismantling via detachable connections, excellent recyclability as well as a general acceptance by end users.This practical volume offers an overview, from the planning process to assembly, while contemporary examples show that building with room modules facilitates heretofore unimagined, multi-layered and differentiated architectures.
Keywords: Architektur: Berufspraxis; Wohngebäude; Öffentliche Gebäude; Gewerbliche Bauten; Hardcover; Softcover / Sachbücher/Kunst; Literatur/Architektur; Architecture; Room Modules; Timber construction; Typologies; Urbanisation; Modulbauweise; Holzbau; Raumzellenbau